Rural residence is not a risk factor for frequent mental distress: a behavioral risk factor surveillance survey - Borders Tyrone F; Rohrer James E; Blanton Jimmy (BMC Public Health, 2005)
Abstract Background Residents of rural areas may be at increased risk of mental health problems. If so, public health programs aimed at preventing poor mental health may have to be customized for delivery to rural areas. The purpose of this study was to examine the relationship between residing in a rural area and frequent mental distress, which is one indicator of poor mental health. Methods The Behavioral Risk Factor Surveillance System (BRFSS) survey for the state of Texas was the source of information about obesity, demographic characteristics, and frequent mental distress (FMD). FMD was defined as poor self-rated mental health during at least half of the days in the last month. Adjusted odds for FMD were computed for rural and suburban respondents relative to urban respondents. Results FMD was found to be independently associated with lower education, being younger, being non-Hispanic, being unmarried, and being female. FMD also was associated with being obese or underweight and suburban residence (relative to metro-central city). FMD was not more common among rural respondents than in the metro-central city. Conclusion Rural respondents were not at greater risk of frequent mental distress than urban respondents in this sample. Programs seeking to improve community mental health should target persons with less education and extremes in body weight, along with women and single persons, regardless of whether they live in rural or urban areas.